The Effectiveness of the Goalkeeper in Initiating Attacks for Persik Kediri Football Team - Bimantoro, Dimas Sandya; Purnomo, Ardhi Mardiyanto Indra; Sugito (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
The aim of this study is to determine the effectiveness of the goalkeeper in initiating attacks for the Persik Kediri football team. This type of research is descriptive qualitative. The population includes all goalkeepers from the Persik Kediri football team. Samples were taken using a non-probability sampling technique with a saturated sampling type. Data collection involved match analysis through the video.com application, focusing on the effectiveness of Persik's goalkeepers during build-up play over 90 minutes in 8 home matches in the first round of BRI Liga 1 from July to October 2023. Subsequently, the data was processed and a comparison table was created between Persik and the visiting teams using match statistics tables over 90 minutes. The results of the study show that build-up play is highly effective for a team in initiating attacks, as it leads to an increased number of passes and opportunities for goals. It is evident from the statistical tables that Persik's goalkeepers consistently performed build-up play more than 10 times per match. Knowing that build-up play is highly effective, coaches can design and implement this tactic in future matches. This technique also enhances the goalkeeper's confidence when initiating attacks.